‘Political gladiators’ on Facebook in Zimbabwe: a discursive analysis of intra-Zimbabwe African National Union -PF cyber wars; Baba Jukwa versus Amai Jukwa - Chibuwe, Albert; Ureke, Oswelled (SAGE Publications, 2021)
Social media have been hailed as liberative in contexts of political repression. In Zimbabwe, there are emergent debates on the possibilities of using Facebook to ‘democratise’ political space. But the use of Facebook to settle personal political scores or to relentlessly attack political opposition seemed to have escaped academic scrutiny. This study looks at the use of Facebook by opposing camps in Zimbabwe’s July 2013 election to attack each other, as well as the challenges posed by this scenario. It looks at Baba Jukwa and Amai Jukwa’s pages on Facebook. The study is grounded in the concepts of freedom of expression, the public sphere and democracy. Semiotic analysis and critical discourse analysis were used to analyse the posts by Baba Jukwa and Amai Jukwa. The study sought to explore how the Internet’s liberative potential enhanced by free entry and exit and the ability to remain anonymous impacts on Baba Jukwa and Amai Jukwa’s discourses on Facebook. It revealed that the two pages make use of personal attacks on ‘targets’, and the resultant polarisation is often mirrored in the mainstream media. The study concludes that even though Facebook provides an alternative public sphere, it can also be ‘pulverised’ by irrational debates.